EKSISTENSI PEREMPUAN DALAM NOVEL PEREMPUAN BATIH KARYA A.R. RIZAL - Arriyanti Usman (Balai Bahasa Kalimantan Barat, 2021)
This research aims to describe the form of marginalization as the others and the form of resistance as a form of existence in the novel Perempuan Batih by A. R. Rizal. It’s based on the approach of existentialist feminism Simone de Beauvoir. The data of this study are descriptions which reveal the forms of marginalization as others and resistance as a form of existence in the novel Perempuan Batih. Data collection is done by reading, recording, and making data corpus techniques. Research data were analyzed using Simone de Beauvoir's existentialist feminism theory. The results of research conducted in 2019 found that the form of marginalization as others in the novel Perempuan Batih was a condition experienced by women whose position was always seen as not absolute. There are two forms of marginalization as others. First, differences in the position of women and men. Secondly, women's violence in terms of services in marriage. The form of resistance as a form of existence of a female character shows what is experienced by a female character who is related to other people and their environment to show and strengthen their existence as a woman. This form of existence can be seen from female figures who try to manifest themselves by working and showing their existence in society.